Missing entrepreneurs: the importance of attitudes and control in shaping entrepreneurial intentions in Russia - Aleksandrova, E; Gerry, CJ; Verkhovskaya, O (Emerald, 2019)
Purpose: Compared with other emerging and former command economies, Russia has low levels of entrepreneurial activity and exceptionally low levels of reported entrepreneurial intentions. Drawing on the theory of planned behaviour (TPB), this paper aims to examine the determinants of entrepreneurial intentions in Russia.